Exploring the Most Challenging Academic IELTS Tested Skills for Indonesian Test Takers - Awaluddin Syamsu; Muhammad Yunus; Astri Arsi Ismail; Dewi Pratiwi Oktavia Bahtiar (Hasanuddin University, 2024)
Academic IELTS test has been widely used by Indonesia people to indicate their academic English proficiency. According to the IELTS official website report 2022, Indonesian people found that writing test as the lowest average score. This study aimed to examine the most difficult test according to the Indonesian test taker’s perception and score result. The study also explored the reasons why they performed lowest in a particular skill. There were 17 Indonesian people who have taken academic IELTS responded our survey. They were from Sulawesi, Java, Sumatra, and Kalimantan with different academic background from fresh graduates of senior high schools and master’s graduates. The open-ended question responses were analyzed thematically to find out the challenges the test takers encountered. The result showed that according to the student’s perception and score in each band, some students found listening, reading and speaking as the most difficult skill however majority experienced writing as the most challenging skill. There were five reasons for their poor performance in writing test, they are less writing practice, lack of vocabulary, poor understanding on academic writing structure, time constrain, and unfamiliar topics. The findings of the research should be considered and become a topic of development for Indonesian people who plan to take academic IELTS test.